Association between hypogonadism and reproductive tissue steroid-producing cells antibody in men with positive MAR test IgG and diabetes mellitus type 1 - Roman V. Rozhivanov (Endocrinology Research Centre, 2019)
BACKGROUND: Autoimmune hypogonadism is frequently taped in men with positive direct mixed agglutination reaction antisperm antibodies IgG test (MAR test IgG). AIMS: Тo assess pathogenetic factor of autoimmune hypogonadism in men with positive MAR test IgG and diabetes mellitus type 1 (DM1). MATERIALS AND METHODS: A retrospective study included 97 patients with positive direct MAR test IgG: 30 men with DM1 and 67 – without DM. Assessment included testosterone level and titer of summary reproductive tissue steroid-producing cells antibody (LCA). Statistically significant differences were p<0,05. RESULTS: 43% of men with DM1 have abnormal LCA titer and it was significantly higher than in patients without DM – 21%. In both groups testosterone level was significantly lower in men with abnormal LCA titer than in patients with normal antibodies titer. Frequency of hypogonadism in men with abnormal LCA titer was significantly higher than in patients with normal antibodies titer also in both groups. There were no significantly differences of MAR test IgG in patients with normal and abnormal LCA titer. CONCLUSIONS: Autoimmune hypogonadism is a common complication in men with DM1 and positive MAR test IgG and it’s strongly associated with high titer of summary reproductive tissue steroid-producing cells antibody.